Thinking forensics: Cognitive science for forensic practitioners. Issue 2 (March 2017) - Edmond, Gary; Towler, Alice; Growns, Bethany; Ribeiro, Gianni; Found, Bryan; White, David; Ballantyne, Kaye; Searston, Rachel A.; Thompson, Matthew B.; Tangen, Jason M.; Kemp, Richard I.; Martire, Kristy
Abstract: Human factors and their implications for forensic science have attracted increasing levels of interest across criminal justice communities in recent years. Initial interest centred on cognitive biases, but has since expanded such that knowledge from psychology and cognitive science is slowly infiltrating forensic practices more broadly. This article highlights a series of important findings and insights of relevance to forensic practitioners. These include research on human perception, memory, context information, expertise, decision-making, communication, experience, verification, confidence, and feedback. The aim of this article is to sensitise forensic practitioners (and lawyers and judges) to a range of potentially significant issues, and encourage them to engage with research in these domains so that they may adapt procedures to improve performance, mitigate risks and reduce errors. Doing so will reduce the divide between forensic practitioners and research scientists as well as improve the value and utility of forensic science evidence. Highlights: Includes ten themes from cognitive scientific endeavours applied to forensics. Covers expertise, memory, bias, decision-making, feedback, and communication. Contains insights that challenge commonly held beliefs about human performance. Tailored for and readily accessible to forensic practitioners, lawyers, and judges.